Air‐Sea Interactions and Water Mass Transformation During a Katabatic Storm in the Irminger Sea. Issue 5 (28th April 2022) - Gutjahr, O.; Jungclaus, J. H.; Brüggemann, N.; Haak, H.; Marotzke, J.
Abstract: We use a global 5‐km resolution model to analyze the air‐sea interactions during a katabatic storm in the Irminger Sea originating from the Ammassalik valleys. Katabatic storms have not yet been resolved in global climate models, raising the question of whether and how they modify water masses in the Irminger Sea. Our results show that dense water forms along the boundary current and on the shelf during the katabatic storm due to the heat loss caused by the high wind speeds and the strong temperature contrast. The dense water contributes to the lightest upper North Atlantic Deep Water as upper Irminger Sea Intermediate Water and thus to the lower limb of the Atlantic Meridional Overturning Circulation (AMOC). The katabatic storm triggers a polar low, which in turn amplifies the near‐surface wind speed due to the superimposed pressure gradient, in addition to acceleration from a breaking mountain wave. Overall, katabatic storms account for up to 25% of the total heat loss (20 January 2020 to 30 September 2021) over the Irminger shelf of the Ammassalik area. Resolving katabatic storms in global models is therefore important for the formation of dense water in the western boundary current of the Irminger Sea, which is relevant to the AMOC, and for the large‐scale atmospheric circulation by triggering polar lows. Plain Language Summary: Katabatic storms are outbursts of cold air associated with strong winds from coastal valleys of Greenland, in particular from the Ammassalik valleys in southeast Greenland. These storms are not resolved in global climate models because of their small spatial extent. However, they are important for the formation of dense water on the Irminger Sea shelf, because they induce a substantial heat loss from the coastal water. In this study, we resolve katabatic storms for the first time in a global climate model and analyze the water transformation caused by a single storm before quantifying the importance of katabatic storms for the entire simulation period. We find that a water mass is formed during the katabatic storm that is dense enough to contribute to the cooling and sinking of the global conveyor belt in the subpolar North Atlantic. Overall, katabatic storms account for up to 25% of the heat loss over the Irminger shelf of the Ammassalik area. Key Points: For the first time, the direct effect of a katabatic storm on the Irminger Sea has been simulated in a global climate model The katabatic storm induces strong heat loss and dense water formation over the Irminger shelf (Sermilik Trough) and in the boundary current Dense water forming in the western boundary current during katabatic storms contributes to the lightest upper North Atlantic Deep Water